2023
DOI: 10.1186/s40001-023-01108-4
|View full text |Cite|
|
Sign up to set email alerts
|

N7-methylguanosin regulators-mediated methylation modification patterns and characterization of the immune microenvironment in lower-grade glioma

Abstract: N7-methylguanosine (m7G) modification signature has recently emerged as a crucial regulator of tumor progression and treatment in cancer. However, there is limited information available on the genomic profile of lower-grade gliomas (LGGs) related to m7G methylation modification genes’ function in tumorigenesis and progression. In this study, we employed bioinformatics methods to characterize m7G modifications in individuals with LGG from The Chinese Glioma Genome Atlas (CGGA) and The Cancer Genome Atlas (TCGA)… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…EIF4E has been demonstrated to participate in the translation of viral mRNA and the proliferation of infected cells [ 49 ]. SARS-CoV-2 can effectively replicate in target cells by utilizing the ERK/MNK1/EIF4E pathway [ 50 , 51 ]. Extensive research has found that EIF4E2 plays a crucial role in tumor progression and metastasis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…EIF4E has been demonstrated to participate in the translation of viral mRNA and the proliferation of infected cells [ 49 ]. SARS-CoV-2 can effectively replicate in target cells by utilizing the ERK/MNK1/EIF4E pathway [ 50 , 51 ]. Extensive research has found that EIF4E2 plays a crucial role in tumor progression and metastasis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, PD-1 and CTLA-4 were overexpressed as well [133,138]. Analogous studies in GC, CRC and lower-grade glioma (LGG) showed the overexpression of PD-L1 in patients with high m7G level [105,145,146], and the other immune checkpoint of tumor cells, CD276 showed same outcomes [147]. Consequently, m7G modification emerged as a predictive factor for the immunological response to anti-PD-L1 therapy [116,146].…”
Section: M7g Modification Impact the Immune Checkpoints Of Tumor Cellsmentioning
confidence: 96%
“…Analogous studies in GC, CRC and lower-grade glioma (LGG) showed the overexpression of PD-L1 in patients with high m7G level [105,145,146], and the other immune checkpoint of tumor cells, CD276 showed same outcomes [147]. Consequently, m7G modification emerged as a predictive factor for the immunological response to anti-PD-L1 therapy [116,146]. These findings underscored the influence of m7G modification on the expression of immune checkpoints in tumor cells, positioning it as a potential biomarker or therapeutic target for immunotherapy.…”
Section: M7g Modification Impact the Immune Checkpoints Of Tumor Cellsmentioning
confidence: 98%
See 1 more Smart Citation
“…This regulatory mechanism plays significant roles in cell fate, proliferation, metabolism, and pathological processes. Given their importance, a deeper understanding of the role of epitranscriptomic modifications in the pathogenesis of tumors, including gliomas, is critical for the development of novel diagnostic and therapeutic approaches [6][7][8][9]. Epigenetics is a complex process involving various modifications such as histone modification, chromatin remodeling, nucleosome localization, DNA methylation, and RNA modification.…”
Section: Introductionmentioning
confidence: 99%